Essential of pediatric nursing - Kyle, Terri; Carman, Susan (Wolter Kluwer/Lippincott Williams & Wilkins Health, 2013)
Promotes confidence in pediatric nursing by growing and developing students' understanding of child and family care. Building on foundational concepts of adult nursing, this title helps students to learn techniques of atraumatic care and patient teaching, and methods of communicating with children and their families